Tren Penelitian Inovasi Manajemen Pembelajaran Pendidikan Agama Islam dalam Jurnal PAI di Indonesia: dari Desain Penelitian Hingga Analisis Data - M Rizqon Al Musafiri (Southeast Asian Journal of Islamic Education Management, 2022)
In this modern era, education is an important means of producing a competent society for the 21st century. This study uses content analysis in several Islamic Religious Education journals published in Indonesia in 2010-2022. This study aims to collect information related to Islamic education learning innovations in Indonesia. This research study uses the principle of content analysis by focusing on findings from various studies that have been published in scientific journals in Indonesia. This research method uses literature study. The data source for this research was collected from the results of content analysis of Islamic Religious Education articles. All articles were taken from the Journal of Islamic Religious Education which was registered on the Science and Technology Index (SINTA) in July 2022. The trend found was an increase starting in the last four years. Among the hundreds of published studies, it was found that quantitative research was the most common. Grade VIII students were the most research subjects chosen by the researchers. PBL is a treatment that has been extensively researched in Islamic education learning innovation research. While the t-test is the instrument that is often used in this study.  Kata Kunci: Innovation, Islamic religious Education, Information and technology